Effects of index card match and card sort on reading comprehension and collaboration - Fatma Atik Mulyani; Supartinah Supartinah (Fakultas Ilmu Pendidikan, Universitas Negeri Yogyakarta, 2024)
This study investigated the effects of Index Card Match (ICM) and Card Sort (CS) learning models on fourth-grade students’ reading comprehension and collaboration skills. Using a quasi-experimental pretest–posttest non-equivalent group design, the study involved 54 students from SDN 1 Depok, assigned to ICM (n = 27) and CS (n = 27) groups. Data were collected through reading comprehension tests, collaboration questionnaires, observations, and interviews, and validated using expert judgment, Pearson product–moment correlation, and Cronbach’s Alpha. Data analysis employed descriptive statistics, paired t-tests, independent t-tests, and MANOVA. Results showed that both models significantly improved students’ reading comprehension and collaboration. ICM produced greater gains in comprehension, while CS more effectively enhanced collaboration. These findings highlight the value of cooperative learning in supporting literacy and social skills within the Merdeka Curriculum, and position ICM and CS as effective instructional strategies for strengthening primary students’ academic and collaborative competencies.